1940 NM ENDOVENOUS LASER IN CLINICAL PRACTICE: INITIAL RESULTS AND HISTOLOGICAL FINDINGS FROM A 1940 NM-TREATED GSV TRIBUTARY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background: Endovenous laser treatment (EVLT) has evolved since its introduction in the late 1990s, with various wavelengths and fiber designs improving efficacy and patient safety. Lasers with wavelengths around 2 μm, including 1920 and 1940 nm, offer promising outcomes due to enhanced absorption by the venous wall and reduced energy requirements. Objective: To evaluate the clinical effectiveness and histological impact of a 1940 nm laser generator for the treatment of varicose veins, including tributaries, and compare its outcomes with existing protocols. Methods: From September 2023 to February 2025, 603 EVLA procedures were performed using a 1940 nm laser in 490 patients. Power settings ranged from 2.5 to 6 W, with a linear endovenous energy density (LEED) of 20–97 J/cm. Histological analysis was conducted on vein segments exposed to 0, 20, 40, 60, and 80 J/cm at 4 W pullback, including a large tributary vein and routine mini-phlebectomies under ultrasound guidance. Results: At 1, 6, and 12 months, target vein occlusion was 100%, and complete vein resorption was observed in 87% of patients within 3–6 months. No incidences of deep vein thrombosis, EHIT, skin burns, or clinically significant hematomas occurred. Mild paresthesia was reported in 5.6% of cases, primarily at mini-phlebectomy sites. Histological findings indicated no significant thermal damage below 40 J/cm, while substantial asymmetrical damage was evident at 60 J/cm and higher. Conclusions: The 1940 nm laser demonstrates high safety and efficacy profiles for both truncal and tributary varicose veins, allowing lower power and LEED than conventional 1.5 μm systems. These parameters reduce postoperative side effects and permit safe treatment near superficial nerves, lymphatic structures, and skin.